Applied statistics of India - Asthana, B.N.; Srivastava,S.S. (Allahabad, 1969)
This revised and enlarged edition of the book gives a critical account of the various official statistics collected in India. These statistics relate to consumption, production, exports, imports, prices, wages, transportation, and communications, and national income. A good deal of discussion is also devoted to National Sample Surveys and planning of statistical enquiries.
Keywords: Demography